2021
DOI: 10.34172/apb.2022.021
|View full text |Cite
|
Sign up to set email alerts
|

CEP55 Inhibitor: Extensive Computational Approach Defining a New Target of Cell Cycle Machinery Agent

Abstract: Purpose: Centrosomal protein 55 (CEP55) is a pivotal protein for cytokinesis during cell division. This study aimed to provide a comprehensive information about the CEP55 gene, including its expression pattern in several cancer types, conduct functional domain analysis across species, and perform a computational approach for potential inhibitors of CEP55. Methods: The expression levels of CEP55 in different cancers were analyzed using the Oncomine and TCGA databases. Evolutionary analysis of the CEP55 gene in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 33 publications
(32 reference statements)
0
4
0
Order By: Relevance
“…CEP55 is a key protein involved in cytokinesis during cell division and is specifically expressed in testis and various types of cancers but not in normal cells [51][52][53]. It has been proposed as a candidate for peptide vaccine therapy in cancers like colorectal carcinoma and breast carcinoma [52,54,55].…”
Section: Discussionmentioning
confidence: 99%
“…CEP55 is a key protein involved in cytokinesis during cell division and is specifically expressed in testis and various types of cancers but not in normal cells [51][52][53]. It has been proposed as a candidate for peptide vaccine therapy in cancers like colorectal carcinoma and breast carcinoma [52,54,55].…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies already identified CEP55 as potential target for anticancer therapies. Although, no specific small molecule inhibitors against CEP55 exist to our knowledge, first computational approaches for the design of future drugs have been performed [ 58 ]. However, alternative approaches targeting upstream regulatory mechanisms of CEP55 may also present possible strategies to block its tumor-supporting properties.…”
Section: Discussionmentioning
confidence: 99%
“…Over the past decades, this has been the most common method of new drug discovery and has given birth to a number of batches of antitumor drugs entering clinical studies [60][61][62]. Given the role of CEP55, we refined and screened potential compounds as new therapeutic strategies [63]. Our analysis from the RNAactDrug and cMap databases revealed that compounds including AZD7762, bleomycin, midostaurin, afatinib, and tanespimycin significantly reduced CEP55 mRNA levels.…”
Section: Discussionmentioning
confidence: 99%